The Opportunities of Crises and Emergency Risk Communication in Activities of Serbian Public Health Workforce in Emergencies - L Ćurčić; *V Radović (Tehran University of Medical Sciences, 2012)
Background: The aim of the study was a recommendation and establishment the concept of the appropriate communication between public health, other competent services and population in emergency as the corner stone which guarantee that all goals which are important for community life will be achieved.Methods: We used methodology appropriate for social science: analyses of documents, historical approach and comparative analysis.Results: The finding shows the urgent need for accepting of crises and emergency risk communication principles, or some similar concepts, in Serbia, and implementing effective two way communication especially in multiethnic region.The pragmatic value of the paper lays in information about the recent improvement of health workforce and emergency services in emergencies using new concept of communication and as source of numerous usefuldocuments published in USA and few recent Serbian examples.Conclusion: Health workforce has significant role in the process of protection of population in emergencies. Policy makers should work on finding a way to improve their coordination and communication, creating new academic programs, providing of adequate training, and financial means in order to give them different role in society andprovide visibility. From other side health workforce should build back to the citizen trust in what they are doing for society welfare using all their skills and abilities.